The Evolution of the Role of the National Parliaments in the Treaties of the Europian Union - Beqiraj (Mihani), Pranvera (European Journal of Multidisciplinary Studies, 2016)
This paper elaborates the evolving role of national parliaments in the different stages of the European integration process. The Review begins with the first stage (the foundation of the European Union) where national parliaments showed no or little interest in the matters of Community, and then the impact of Single European Act, following the first changes in the Maastricht Treaty, through the two Declarations attached to it and then the Protocol to the Treaty of Amsterdam. Finally the paper focuses on the changes and innovations presented in the Lisbon Treaty which will enhance the role of national parliaments in the European Union governance. For this purpose, the paper analyzes chronologically the rights that national parliaments had before the Lisbon Treaty and the new role of national parliaments after the Lisbon Treaty came into force.